Merdeka BelajarKampus Merdeka (MBKM) to strengthen the culture and citizenship literacy of EFL pre-service teachers - Dewi, Silvi Listia; Misnawati, Misnawati; Hayati, Rahmi; Zuhra, Intan; Misnar, Misnar (Studies in English Language and Education, 2023)
The purpose of this study is to explain and describe the role of the Merdeka BelajarKampu Merdeka (MBKM) or the Independent Learning Program in enhancing the culture and citizenship literacy of EFL (English as a Foreign Language) pre-service teachers at Universitas Almuslim, Indonesia, through the PERMATA-SAKTI Program, a student exchange program. This research employed a mixed method. The respondents of this study were prospective EFL teachers who participated in the program. Five informants were interviewed extensively to collect qualitative data. The interviews were transcribed and the results were analyzed through thematic analysis. A number of 35 pre-service EFL teachers filled in a closed-ended questionnaire to collect quantitative data. These data were analyzed descriptively. The findings of this study indicated that the program could strengthen the cultural and citizenship literacy of EFL pre-service teachers by introducing culture and diversity through the online learning process. The active combined learning process revealed the values of solidarity, tolerance, diversity, and unity. EFL pre-service teachers developed an attitude of mutual respect through a dynamic learning process involving diverse languages, races, ethnicities, religions, and worldviews. This study concluded that the PERMATA-SAKTI Program effectively strengthened the EFL pre-service teachers cultural and citizenship literacy.